Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.